RESPON CABAI (Capsicum annum L.) TERHADAP PENGGUNAAN PUPUK ORGANIK CAIR DAN PUPUK HAYATI MIKORIZA - Rosmiah, Rosmiah; Paridawati, Ika; Marlina, Neni; Iskandar, Sutarmo; Dali, Dali; Alfando, Febri; Ezward, Chairil (Jurnal Agro Indragiri, 2024)
Red chili (Capsicum annuum L.) is one of the commodities vegetables that have high economic value. One attempt to increase the growth and yield of chili plants by using liquid organic fertilizer and mycorrhizal biological fertilizer. This research aims to determine the best dosage of liquid organic fertilizer and mycorrhizal biological fertilizer on the yield of red chili (Capsium annum L.). The research was carried out on land of Agriculture of Palembang City, South Sumatra Province. The research period was carried out from February to June 2023. The research used a Randomized Group Factorial Design (RAKF) with 9 treatments and 3 replications. The first factor is liquid organic fertilizer from vegetable waste according to the treatment, namely O1 = 5 ml/L, O2 = 10 ml/L and O3= 15 ml/L. The second factor is the provision of Mycorrhizal biofertilizer (M) which consists of 4 treatment dose levels, namely M0 = 0 g/ta (without mycorrhiza), M1 = 2.5 g/ta, M2 = 5 g/ta, M3 = 7.5 g /ta. The observation parameters in this study were chili weight per plant (g), chili weight per plot (g) and number of productive brances (brances). The results of the research showed that treatment with a POC dose of vegetable waste of 5 ml/l of water with mycorrhizal biological fertilizer of 2.5 g/lot had the highest influence on chili plant production of 48.33 g/plot or the equivalent of 193,32 kuintal/ha.